ILLOCUTIONARY AND PERLOCUTIONARY ACTS IN THE NOVEL "THE BOOK OF LOST THINGS" BY JHON CONNOLY - Firman Setiawan; Soenardjati Djajanegara (INFERENCE: Journal of English Language Teaching, 2020)
Abstract: Illocutionary act is an important part in order to understand the speech acts. It is related to the speaker’s intention in the conversation, and it can be seen from the utterances. In contrast, Perlocutionary act is the effect of the utterance which the speaker said to the hearer. This act does not consist of certain things in certain ways, but it is having certain effects. The literary works of concern for this study is The Book of Lost Things novel. The purpose of this paper is to describe the Illocutionary and Perlocutionary acts employed by the characters in the novel. The finding of this study indicates that the characters in The Book of Lost Things employed all types of Illocutionary acts and responding to that using Perlocutionary acts. It can be concluded that the used of Illocutionary and Perlocutionary acts can be found in this novel.Key Words: illocutionary act; perlocutionary act; speech act; the book of lost things.